Estimation of solutions of nonautonomous systems - Puzyrev, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study the problem of using the direct Lyapunov method to get estimates for solutions of a system of ordinary differential system in general form. Theorems on asymptotic stability and behavior of solutions are proved.